2005
DOI: 10.1111/j.1478-3231.2005.01201.x
|View full text |Cite
|
Sign up to set email alerts
|

Design‐based stereological estimation of hepatocyte number, by combining the smooth optical fractionator and immunocytochemistry with anti‐carcinoembryonic antigen polyclonal antibodies

Abstract: The strategy here presented provides a reliable method for accessing the N of HEP (distinguishing MnHEP from BnHEP) in situations in which these parameters are relevant, namely for evaluating the magnitude of an hyperplastic liver response from its very early onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 38 publications
3
46
1
Order By: Relevance
“…Indeed, and facing some established criteria (e.g., Ikeda et al 1995;Majno and Joris 1995), we observed typical morphological aspects of apoptosis attaining hepatocytes. However, the quantification of such phenomena was not a target when we began the study, but it can be addressed in the future, e.g., by combining immunochemistry with an optical fractionator design in paraffin sections (Marcos et al 2004(Marcos et al , 2006. Anyway, our data support that a numerical decline of hepatocytes in females from vitellogenesis to post-spawning occurred.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Indeed, and facing some established criteria (e.g., Ikeda et al 1995;Majno and Joris 1995), we observed typical morphological aspects of apoptosis attaining hepatocytes. However, the quantification of such phenomena was not a target when we began the study, but it can be addressed in the future, e.g., by combining immunochemistry with an optical fractionator design in paraffin sections (Marcos et al 2004(Marcos et al , 2006. Anyway, our data support that a numerical decline of hepatocytes in females from vitellogenesis to post-spawning occurred.…”
Section: Discussionsupporting
confidence: 61%
“…Such concepts have been largely implemented in neuroscience-to the point that editors urged authors and reviewers to adhere to the so-called ''stereologically based unbiased estimates'' (Coggeshall and Lekan 1996;Saper 1996). Their use in hepatology is apparently confined to only a few studies, made in rats (Jack et al 1990a, b;Marcos et al 2003Marcos et al , 2004Marcos et al , 2006 and in brown trout (Rocha et al , 2001; therefore, more applications are needed to gain new insights using more powerful quantitative tools.…”
Section: Introductionmentioning
confidence: 96%
“…Six random dissector pairs were analyzed for each specimen. The collagen fibers, fat globule and hepatocytes absolute and relative volume (V and Vv to [cf], [fg], and [h], respectively) as well as the absolute number of hepatocytes (N[h]) were determined as the product of the volume densities of these structures and the numerical density of the hepatocytes by the hepatic volume previously measured (Aguila et al, 2003;Marcos et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…[27] Since the recent development of stereological quantification methods, a large amount of numerical data has been readily obtained. [28,29] In the histological step of our study, dilatation of glomerular capillaries and large blood vessels was seen. In addition to tubular deformations, hyaline accumulation, necrosis, and vacuolar degenerations supported our stereological data.…”
Section: Discussionmentioning
confidence: 99%